Recombinant expression and preliminary characterization of a synthetic L‐asparaginase from the marine bacterium Pseudoalteromonas tetraodonis GFC in Escherichia coli BL21 (DE3) - Pertiwi, Wulan; Tohari, Taufik Ramdani; Suhada, Qori Atur Rodiah; Zahira, Tiara; Nugraha, Nadila Suci (Indonesian Journal of Biotechnology, 2026)
The marine environment represents a promising source of diverse enzymes produced by marine microorganisms, including L‐asparaginase. This has been widely studied due to its ability to hydrolyze extracellular L‐asparagine, an amino acid required for the growth of certain cancer cells. In this study, a synthetic L‐asparaginase gene derived from the marine bacterium Pseudoalteromonas tetraodonis GFC was recombinantly expressed in Escherichia coli BL21 (DE3). The gene was cloned into the pD861‐SR expression vector and transformed into E. coli BL21 (DE3). Positive transformants were confirmed by restriction digestion using SapI and Sanger sequencing. Recombinant protein expression was induced with L‐rhamnose under the control of the rhaBAD promoter. The expressed L‐asparaginase was then purified using Ni‐Sepharose affinity chromatography followed by membrane dialysis, yielding a protein purity of 73.6%. SDS‐PAGE analysis revealed a prominent protein band at approximately 37 kDa, corresponding to the expected molecular weight of recombinant L‐asparaginase. Enzymatic activity was evaluated using the Nessler method, and the purified enzyme exhibited a specific activity of 5.863 U/mg. These results demonstrate the successful recombinant expression and preliminary functional validation of L‐ asparaginase from P. tetraodonis GFC in E. coli, providing a basis for further optimization and characterization in future studies.